2014
DOI: 10.2174/1568026614666141112094058
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Bile Acids: Targeting Farnesoid X Receptor (FXR) with Natural and Synthetic Ligands

Abstract: The modulation of FXR receptor remains an attractive area in drug discovery to develop novel therapeutic opportunities for liver and metabolic disorders. Despite the large variety of FXR ligands reported so far, only a very restricted number of agonists have entered in clinical settings. In this review article we provide the reader with an overview on the different classes of natural and synthetic ligands that have been developed by academic groups and pharmaceutical companies to target FXR. We discuss their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 121 publications
0
28
0
Order By: Relevance
“…As evidenced by the above discussion and by the previous published reviews [25,44,45], during the past years wide medicinal chemistry protocols have been carried out in order to identify and to develop potent and selective ligands targeting FXR. Many of these ligands have agonistic activity and have been largely used as tools to dissect FXR biology and FXR regulated signaling and transcriptional events.…”
Section: Fxr Antagonistsmentioning
confidence: 94%
See 1 more Smart Citation
“…As evidenced by the above discussion and by the previous published reviews [25,44,45], during the past years wide medicinal chemistry protocols have been carried out in order to identify and to develop potent and selective ligands targeting FXR. Many of these ligands have agonistic activity and have been largely used as tools to dissect FXR biology and FXR regulated signaling and transcriptional events.…”
Section: Fxr Antagonistsmentioning
confidence: 94%
“…Thus, several groups from academy and industry have harnessed the chemical space around the stilbene moiety, the position of the carboxyl group on the terminal aryl unit, the nature of classical chlorophenyl linker, whereas the central isoxazole core, with the isopropyl group at C-5 and the 2,6-dihalogen-substituted phenyl moiety at C-3, has been conserved. All related patent applications date before the year 2010 and have been largely reviewed in previous contributes [25,44,45].…”
Section: Non-steroidal Fxr Agonistsmentioning
confidence: 99%
“…FXR is also expressed in HSCs and activation of FXR in HSCs is associated with significant decrease in collagen production [64]. Activation of FXR occurs via binding with bile acids such as deoxycholic or lithocholic acid, although many synthetic ligands are also known [65]. However, most FXR ligands failed the preclinical and clinical assessment because of poor pharmacokinetics or toxicity issues.…”
Section: Developments In Targeted Therapy Related To Liver Fibrosismentioning
confidence: 99%
“…GR-MD-02 (galactoarabino-rhamnogalacturonate) is a potent inhibitor of Galectin-3 [96] that showed remarkable therapeutic effects in thioacetamide-induced liver fibrosis in rats [97] and was submitted for 3 clinical studies concerning liver fibrosis. Phase 1 study evaluating safety of GR-MD-02 in patients with nonalcoholic steatohepatitis (NASH) and advanced fibrosis is already completed [65, 98, 99]. Results showed that the drug was safe and well tolerated in NASH patients with liver fibrosis and demonstrated improvement in fibrosis and inflammation [100–102].…”
Section: Developments In Targeted Therapy Related To Liver Fibrosismentioning
confidence: 99%
See 1 more Smart Citation